Difference between revisions of "009B Sample Midterm 2, Problem 4"
Jump to navigation
Jump to search
Line 7: | Line 7: | ||
!Foundations: | !Foundations: | ||
|- | |- | ||
− | |Integration by parts tells us <math style="vertical-align: -15px">\int u~dv=uv-\int v~du.</math> | + | |'''1.''' Integration by parts tells us <math style="vertical-align: -15px">\int u~dv=uv-\int v~du.</math> |
|- | |- | ||
− | |How would you integrate <math style="vertical-align: -15px">\int e^x\sin x~dx?</math> | + | |'''2.''' How would you integrate <math style="vertical-align: -15px">\int e^x\sin x~dx?</math> |
|- | |- | ||
| | | | ||
Line 34: | Line 34: | ||
|- | |- | ||
| | | | ||
− | ::Notice, we are back where we started. | + | ::Notice, we are back where we started. |
|- | |- | ||
| | | | ||
− | ::we get <math style="vertical-align: -13px">2\int e^x\sin (x)~dx\,=\,e^x(\sin(x)-\cos(x)).</math> | + | ::So, adding the last term on the right hand side to the opposite side, we get |
+ | |- | ||
+ | | | ||
+ | ::<math style="vertical-align: -13px">2\int e^x\sin (x)~dx\,=\,e^x(\sin(x)-\cos(x)).</math> | ||
|- | |- | ||
| | | | ||
Line 47: | Line 50: | ||
!Step 1: | !Step 1: | ||
|- | |- | ||
− | |We proceed using integration by parts. Let <math style="vertical-align: -5px">u=\sin(2x)</math> and <math style="vertical-align: 0px">dv=e^{-2x}dx</math> | + | |We proceed using integration by parts. Let <math style="vertical-align: -5px">u=\sin(2x)</math> and <math style="vertical-align: 0px">dv=e^{-2x}dx.</math> Then, <math style="vertical-align: -5px">du=2\cos(2x)dx</math> and <math style="vertical-align: -13px">v=\frac{e^{-2x}}{-2}.</math> |
|- | |- | ||
|So, we get | |So, we get | ||
|- | |- | ||
− | | | + | | |
+ | ::<math>\begin{array}{rcl} | ||
+ | \displaystyle{\int e^{-2x}\sin (2x)~dx} & = & \displaystyle{\frac{\sin(2x)e^{-2x}}{-2}-\int \frac{e^{-2x}2\cos(2x)~dx}{-2}}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{\frac{\sin(2x)e^{-2x}}{-2}+\int e^{-2x}\cos(2x)~dx.}\\ | ||
+ | \end{array}</math> | ||
|} | |} | ||
Line 57: | Line 65: | ||
!Step 2: | !Step 2: | ||
|- | |- | ||
− | |Now, we need to use integration by parts again. Let <math style="vertical-align: -5px">u=\cos(2x)</math> and <math style="vertical-align: 0px">dv=e^{-2x}dx</math> | + | |Now, we need to use integration by parts again. Let <math style="vertical-align: -5px">u=\cos(2x)</math> and <math style="vertical-align: 0px">dv=e^{-2x}dx.</math> Then, <math style="vertical-align: -5px">du=-2\sin(2x)dx</math> and <math style="vertical-align: -13px">v=\frac{e^{-2x}}{-2}.</math> |
|- | |- | ||
|So, we get | |So, we get | ||
− | |||
− | |||
|- | |- | ||
| | | | ||
+ | ::<math style="vertical-align: -13px">\int e^{-2x}\sin (2x)~dx=\frac{\sin(2x)e^{-2x}}{-2}+\frac{\cos(2x)e^{-2x}}{-2}-\int e^{-2x}\sin(2x)~dx</math>. | ||
|} | |} | ||
Line 73: | Line 80: | ||
|So, if we add the integral on the right to the other side of the equation, we get | |So, if we add the integral on the right to the other side of the equation, we get | ||
|- | |- | ||
− | | | + | | |
+ | ::<math>2\int e^{-2x}\sin (2x)~dx=\frac{\sin(2x)e^{-2x}}{-2}+\frac{\cos(2x)e^{-2x}}{-2}.</math> | ||
|- | |- | ||
|Now, we divide both sides by 2 to get | |Now, we divide both sides by 2 to get | ||
|- | |- | ||
− | | | + | | |
+ | ::<math>\int e^{-2x}\sin (2x)~dx=\frac{\sin(2x)e^{-2x}}{-4}+\frac{\cos(2x)e^{-2x}}{-4}.</math> | ||
|- | |- | ||
− | |Thus, the final answer is <math style="vertical-align: -13px">\int e^{-2x}\sin (2x)~dx=\frac{e^{-2x}}{-4}((\sin(2x)+\cos(2x))+C</math> | + | |Thus, the final answer is |
+ | |- | ||
+ | | | ||
+ | ::<math style="vertical-align: -13px">\int e^{-2x}\sin (2x)~dx=\frac{e^{-2x}}{-4}((\sin(2x)+\cos(2x))+C.</math> | ||
|} | |} | ||
Revision as of 13:57, 18 April 2016
Evaluate the integral:
Foundations: |
---|
1. Integration by parts tells us |
2. How would you integrate |
|
|
|
|
|
|
|
|
|
|
Solution:
Step 1: |
---|
We proceed using integration by parts. Let and Then, and |
So, we get |
|
Step 2: |
---|
Now, we need to use integration by parts again. Let and Then, and |
So, we get |
|
Step 3: |
---|
Notice that the integral on the right of the last equation in Step 2 is the same integral that we had at the beginning of the problem. |
So, if we add the integral on the right to the other side of the equation, we get |
|
Now, we divide both sides by 2 to get |
|
Thus, the final answer is |
|
Final Answer: |
---|